Spolni stereotipi in diskriminacija žensk na trgu dela - Svetek, Mojca (Psihološka obzorja (Ljubljana), 2019)
This paper provides an overview of (social) psychological evidence of the gender-based workplace and labour market discrimination. The article discusses how gender stereotypes produce gendered employee perceptions, workplace expectations and standards of evaluations. It explains which psychological mechanisms are crucial in the maintenance of discrimination in the labour market and summarizes research findings on future development of gender stereotypes. The article mainly refers to the obstacles that women face in accessing management positions, since this issue received the most attention in psychological literature. Nevertheless, the mechanisms of discrimination presented in this review are not limited to the upper layer of the labour market.
Keywords: assessment; atribucije; attribution; delovna uspešnost; delovno mesto; discrimination; diskriminacija; job performance; leaders; ocenjevanje; psihologija dela; sex role attitudes; social psychology; socialna psihologija; spolni stereotipi; vodje; women; work psychology; workplace; ženske